A study on factors contributed towards repeat purchase behavior / Nurasyikin Shaari - Shaari, Nurasyikin (Faculty of Business and Management, 2009)
The decision by customers to re-purchase from the same service provider depends on their past experiences. Customers' repurchase intent depends on the value obtained in their previous transactions such as appropriate performance criteria (benefits), competition, and cost considerations. Future purchase intentions also have a relationship with customer satisfaction overall, customers evaluate future purchase intentions based on the value obtained from previous episodes/contacts, with relationship benefits being a proxy for expectations of future benefits. The main purpose to identify the factors influencing customer to make repeat purchase behaviors, to identify relationship between attribute and repeat purchase behavior, to identify relationship between benefits and repeat purchase behavior, to identify relationship between motivational value and repeat purchase behavior, and to identify relationship between brand loyalty and repeat purchase behavior. This research is conducted by using random sampling. The sampling size would be 38 respondents and all of the questions had been answered. It has been taken conveniently at Digicity (M) Sdn. Bhd., Perinqqit, Malacca. As a conclusion on this research all objectives have successfully been made. Another, some recommendation has been suggested in order to enhance and improve organization performance regarding to repeat purchased behavior